Globalization, re-discovery of the Malay ‘local,' and popular TV fiction through audience narratives - Mohd Muzhafar Idrus,; Ruzy Suliza Hashim,; Raihanah M. M., (Penerbit Universiti Kebangsaan Malaysia, 2016)
The proliferation of TV fiction can be partly explained by TV producers attuning their products to draw audience’s attention. Narratives of love dominate the plots and almost always the good is pitted against the evil, rich against the poor - ultimately the good always wins. The formula may be clichéd, but in places where news of war, terrorism, diseases, violence, and conflicts usually prevail, respite from tumultuous realities of the world can often be found in popular TV fiction. Here, we study three popular Malay TV fiction, Julia, On Dhia, and Adam & Hawa to examine how TV fiction viewers relate to them through personal narratives and focus group interviews. Through their voices, we reveal that despite TV fiction viewers’ constant preoccupation with Western-imposed globalization, the TV fiction set against the backdrop of globalization can encourage the viewers to re-route their ways to re-discover their imaginary ‘good old days’ that are often dismissed, neglected or forgotten.